2012
DOI: 10.2355/isijinternational.52.240
|View full text |Cite
|
Sign up to set email alerts
|

Internal Reversible Hydrogen Embrittlement of Austenitic Stainless Steels Based on Type 316 at Low Temperatures

Abstract: The internal reversible hydrogen embrittlement (IRHE) of austenitic Fe(10-20)Ni17Cr2Mo alloys based on type 316 stainless steels hydrogen-charged to around 40 mass ppm was investigated by performing tensile tests using the slow strain rate technique at temperatures from 80 to 300 K. The susceptibility to IRHE depended on the Ni content. IRHE occurred below a Ni content of 15% (Ni equivalent of 29%), increased with decreasing temperature, reached a maximum at 200 K and decreased with further decreasing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 55 publications
0
5
0
2
Order By: Relevance
“…The effect of temperature on the tensile ductility of 300 series stainless steels in the solution-treated condition was investigated in various studies [3,7,8,[10][11][12][13][14][15][16][17][18][19][20][21]. Some studies reported the reduction of area (RA) measured under the influence of hydrogen [16][17][18][19], but most studies reported the relative reduction of area (RRA) as the ratio of RA measured under the influence of hydrogen and in a control atmosphere, e.g., air, He, or Ar (RRA = RA H2 /RA Control ).…”
Section: Austenitic Stainless Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of temperature on the tensile ductility of 300 series stainless steels in the solution-treated condition was investigated in various studies [3,7,8,[10][11][12][13][14][15][16][17][18][19][20][21]. Some studies reported the reduction of area (RA) measured under the influence of hydrogen [16][17][18][19], but most studies reported the relative reduction of area (RRA) as the ratio of RA measured under the influence of hydrogen and in a control atmosphere, e.g., air, He, or Ar (RRA = RA H2 /RA Control ).…”
Section: Austenitic Stainless Steelsmentioning
confidence: 99%
“…Additionally, alloying up to 10 wt% Mn in 316 grades appeared to have a negligible influence on T HE,max [13]. Analyzing T HE,max as functions of tensile strain rate [3,7,11,[16][17][18][19] (Figure 3c) demonstrated that the hydrogen gas pressure for tests performed in hydrogen gas [3,8,[11][12][13][14][15]21,22] (Figure 3d) and the hydrogen content for tests performed with gaseous [7,10,[16][17][18] or electrolytic [19] precharged specimens ( Figure 3e) showed no significant influence of either parameter within the given parameter ranges. T HE,max of CrMnN austenitic stainless steels was reported to be around 250 K (Figure 3f) [7,18], which is higher than that of 304-and 316-type austenitic stainless steels.…”
Section: Austenitic Stainless Steelsmentioning
confidence: 99%
“…For the type 304 (SA) and 316 (SA and CW) austenitic stainless steels in 105 MPa hydrogen and air, type 316 with higher Ni equivalent shows neither HGE nor IRHE. [27][28][29] Type 304 shows HGE and IRHE; however, its K IH cannot be obtained by static loading method, 26 thus we estimated K IH of 40 MPaÁm 0.5 in 105 MPa hydrogen extrapolated from the data by J-integral method up to hydrogen of 10 MPa based on rising loading method. 23 Design fatigue life in hydrogen by K IH is nearly above 10 4 cycles.…”
Section: Fatigue Life Evaluation For Practical Materialsmentioning
confidence: 99%
“…Analyzing the influence mechanism of internal hydrogen would be even more necessary considering the high hydrogen diffusion coefficient in X80 pipeline steel and the difficulty of studying the effect of internal hydrogen. Two modes of environmental hydrogen inducing HE have been presented: (1) hydrogen penetrates steel and induces internal HE 13,28,29 and (2) the influence of hydrogen on crack propagation behavior. 30,31 The purpose of this work was to investigate the effects of internal hydrogen on hydrogen-induced degradation at a relatively high strain by performing a precharged hydrogen test.…”
Section: Introductionmentioning
confidence: 99%